2012
DOI: 10.1159/000342451
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of 1,025 Severely Ill Patients with Complicated Infections in a German Multicenter Study: Safety Profile and Efficacy of Tigecycline in Different Treatment Modalities

Abstract: This large prospective non-interventional study investigated the effects of tigecycline either as single agent or in combination with other antimicrobial agents in 1,025 patients treated in clinical routine at German hospitals. Sixty-five percent of the patients had APACHE II scores >15, indicating high overall disease severity. Complicated intra-abdominal infections (cIAI) or complicated skin and skin tissue infections (cSSTI) were the most common indications, with Staphylococcus aureus, Enterococcus faecium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 90 publications
(54 reference statements)
3
15
0
6
Order By: Relevance
“…To solve this problem, it is needed to develop a new broad-spectrum antibacterial agent. TGC was initially approved by the US FDA in June 2005 to indicate the treatment of complex skin, soft tissue, and intra-abdominal infections [13,14]. A clinical retrospective study on the efficiency and safety of the TGC treatment as empirical antibiotic therapy was performed in study.…”
Section: Discussionmentioning
confidence: 99%
“…To solve this problem, it is needed to develop a new broad-spectrum antibacterial agent. TGC was initially approved by the US FDA in June 2005 to indicate the treatment of complex skin, soft tissue, and intra-abdominal infections [13,14]. A clinical retrospective study on the efficiency and safety of the TGC treatment as empirical antibiotic therapy was performed in study.…”
Section: Discussionmentioning
confidence: 99%
“…A logistic regression analysis [27] suggested that mortality at 30 days and mortality in the first 2 or 7 days was similar between tigecycline and the comparators, and it highlighted that treatment with tigecycline was not associated with mortality. Mortality rates were consistent with the type of infection and severity of illness [28]. In conventional-dose tigecycline-treated patients with HAP, especially those with VAP, baseline bacteremia was a significant predictor of mortality [29].…”
Section: Discussionmentioning
confidence: 99%
“…Median treatment duration was 8 days for BSI (range 4-17), 9 days for HAP (5-17), 10 days for IAI and CAP (7)(8)(9)(10)(11)(12)(13)(14)(15), 11 days for SSTI and DFI , and 12 days for MSI .…”
Section: Mode and Duration Of Therapymentioning
confidence: 99%
“…Results obtained in the total patient population have been published before [15]. Here, we present data on patients suffering from infections with documented involvement of bacteria exhibiting multidrugresistant phenotypes.…”
mentioning
confidence: 99%